Frailty Hinders Recovery From Influenza and Acute Respiratory Illness in Older Adults. (9th March 2020) - Lees, Caitlin; Godin, Judith; McElhaney, Janet E; McNeil, Shelly A; Loeb, Mark; Hatchette, Todd F; LeBlanc, Jason; Bowie, William; Boivin, Guy; McGeer, Allison; Poirier, André; Powis, Jeff; et al.
Abstract: Background: We examined frailty as a predictor of recovery in older adults hospitalized with influenza and acute respiratory illness. Methods: A total of 5011 patients aged ≥65 years were admitted to Canadian Serious Outcomes Surveillance Network hospitals during the 2011/2012, 2012/2013, and 2013/2014 influenza seasons. Frailty was measured using a previously validated frailty index (FI). Poor recovery was defined as death by 30 days postdischarge or an increase of more than 0.06 (≥2 persistent new health deficits) on the FI. Multivariable logistic regression controlled for age, sex, season, influenza diagnosis, and influenza vaccination status. Results: Mean age was 79.4 (standard deviation = 8.4) years; 53.1% were women. At baseline, 15.0% (n = 750) were nonfrail, 39.3% (n = 1971) were prefrail, 39.8% (n = 1995) were frail, and 5.9% (n = 295) were most frail. Poor recovery was experienced by 21.4%, 52.0% of whom had died. Frailty was associated with lower odds of recovery in all 3 seasons: 2011/2012 (odds ratio [OR] = 0.70; 95% confidence interval [CI], 0.59–0.84), 2012/2013 (OR = 0.72; 95% CI, 0.66–0.79), and 2013/2014 (OR = 0.75; 95% CI, 0.69–0.82); results varied by season, influenza status, vaccination status, and age. Conclusions: Increasing frailty is associated with lower odds of recovery, and persistent worsening frailty is an important adverse outcome of acute illness. Abstract : Serum quantification of hepatitis B core–related antigen and anti–hepatitis B core antibodies could be useful in predicting hepatitis B e antigen seroclearance in patients with human immunodeficiency virus–hepatitis B virus coinfection undergoing long-term tenofovir-containing antiretroviral therapy, but they do not perform better than other, currently available markers.